2019
DOI: 10.1002/hec.3916
|View full text |Cite
|
Sign up to set email alerts
|

Methods for public health economic evaluation: A Delphi survey of decision makers in English and Welsh local government

Abstract: Standard reference case methods recommended for health technology appraisals do not translate well to a public health setting. This paper reports on a Delphi survey designed to elicit views of public health decision makers in England and Wales, about different methodological elements of economic evaluation. This is important as methods should align with the objective function of decision makers. The Delphi survey comprised two rounds, with round 1 allowing open‐ended recommendations in addition to 5‐point Like… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…Furthermore, preventive interventions or public health interventions require financial support and implementation from sectors outside of health (e.g., school-based interventions typically involve the education sector) [ 87 ]. Standard economic evaluation methods commonly applied to health technology assessment may not be transferable to health promotion evaluation and broader frameworks, such as cost-benefit analyses may be required where broader benefits can be captured and measured [ 88 ]. Given the rapid growth of the number of interventions for promoting mental or psychological well-being, and building resilience [ 89 ], economic evaluations with improved methods and capturing intersectoral cost and outcomes of such interventions are needed [ 86 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, preventive interventions or public health interventions require financial support and implementation from sectors outside of health (e.g., school-based interventions typically involve the education sector) [ 87 ]. Standard economic evaluation methods commonly applied to health technology assessment may not be transferable to health promotion evaluation and broader frameworks, such as cost-benefit analyses may be required where broader benefits can be captured and measured [ 88 ]. Given the rapid growth of the number of interventions for promoting mental or psychological well-being, and building resilience [ 89 ], economic evaluations with improved methods and capturing intersectoral cost and outcomes of such interventions are needed [ 86 ].…”
Section: Discussionmentioning
confidence: 99%
“…Costs were considered important by local decision‐makers when making (dis)investment decisions in a recent study conducted in the United Kingdom and Ireland 46 , along with health‐related and well‐being outcomes. Evidence suggests that information on economic considerations such as intervention resource use and costs are perceived to increase the potential for interventions to be implemented on a more widespread basis 47 .…”
Section: Discussionmentioning
confidence: 99%
“…The views of our stakeholders chimed with the findings of other researchers around the preferences of public health decision-makers on economic evaluation. 196 This research found that public health decisionmakers preferred economic evaluations to include costs and effects for different subgroups and different sectors (e.g. health, social care, productivity), as we have included in the workHORSE model.…”
Section: Strength and Limitationsmentioning
confidence: 99%